Identification of genetic/epigenetic biomarkers for supporting decision of VOCs exposure - An, Yu Ri; Kim, Seung Jun; Yu, So-Yeon; Yoon, Hyo-Jung; Song, Mi-Kyung; Ryu, Jae-Chun; Hwang, Seung Yong (KOREAN BIOCHIP SOCIETY-KBCS, 2013)
Ethylbenzene, toluene and xylene are widely used volatile organic compounds (VOCs). VOCs are dangerous to human health or cause harm to the environment. The assessment of VOC exposure maybe carried out through a number of techniques. One of them, the epigenetic biomarker applies a new technology. Environmental epigenetics focuses on how cells or organisms respond to environmental factors to create altered phenotypes or diseases. In this study, our intention was to conduct an investigation of epigenetic biomarkers in VOCs. For the experiment, we used the DNAs and RNAs from VOC exposed human blood and VOCs treated cell lines. Then, we compared the data using microarray fold change, real-time PCR and methylation specific PCR. As a result, we identified five microRNAs (miR-520g, miR-424, miR-210, miR-21, and miR-142-3p), three methylation regions (SERPINB5, ZC3H3, and PCSK6) and four transcripts (CRCT1, RUNX3, PCDH11X, and PCSK6), which could be used as biomarkers for VOCs, becommings the foundation for a system which can predict VOC exposure.
Keywords: VOLATILE ORGANIC-COMPOUNDS; GENE-EXPRESSION; CANCER; WORKERS